Elastomers' wear: Comparison of theory with experiment. (July 2019) - Hakami, F.; Pramanik, A.; Basak, A.K.; Ridgway, N.
Abstract: Wear of elastomers is different and far more complex than that of metallic materials, which arises owing to the effect of various operating parameters as well as physical and mechanical properties of the elastomers. Therefore, the prediction of wear of the elastomers while sliding against rough counterparts is of practical importance. The current study attempts to formulate equations to predict the wear rate of elastomers by identifying and considering the dominant material properties (such as, hardness, tensile strength, and elongation at break) as well as operating variables that control the wear The exponents and coefficient are obtained experimentally, which represent the significance of each parameter. A good correlation is observed between the calculated and measured wear rates. Highlights: Wear equations are developed by considering the dominant mechanical properties of the material and operating variables. The constants of the equations are obtained experimentally, which represent the significance of each parameter. A good correlation is observed between the calculated and measured wear rates.